Editorial. (March 2015) - Alderman, Lyn; Clinton, Janet
'Evaluation is a profession that serves all other professions and draws from a full range of disciplines' (Coryn & Stufflebeam 2014, p. 40). This idea that evaluation is pervasive is an interesting one, and if correct, makes evaluation a discipline that is difficult to define and one whose power is difficult to harness. Stufflebeam and Coryn also argue that society and most of its institutions require formal and systematic evaluation to function successfully. Of course, evaluation needs to be rigorous and make a worthwhile contribution. It is unfortunate that evaluation is not yet embedded or manifested across our society, and often the quality and impact is questionable.